5th Nordic Workshop on Reindeer Research, 30 October - 2 November 1989, Oulo, Finland. 5. nordiske reinforskermøte, 30 oktober - 2 november 1989, Oulu, Finland. - Skjenneberg (ed.), Sven (Rangifer, 1990)
The Fifth Nordic Reindeer Scientist's Meeting, organised by the Nordic Council for Reindeer Research, was held at Oulu, Finland, 30 October - 2 November 1989 and was attended by 62 delegates. The principal themes of the meeting were ' Reindeer Feeds and Feeding' and ' The Economic and Ecological Carrying Capacity of Reindeer Husbandry'.